Financial markets, banking, and monetary policy - Simpson, Thomas D. 1942- (Hoboken, New Jersey John Wiley & Sons, Inc., 2014)
"The current financial model has focused on money as a unique asset that is produced exclusively by commercial banks, and regulated by central banks to achieve their macroeconomic goals. However, as financial systems have evolved in the United States and elsewhere around the globe, what constitutes money has become blurred and such monetary aggregates have become highly unreliable and discarded guides to policy. As a result, central banks have had to turn to a very different approach for achieving macroeconomic goals. This approach instead focuses on influencing the prices of a broad spectrum of financial assets, and thereby the spending behavior of businesses and consumers. They do so by relying on their control over the short-term policy interest rate and its influence on the core element of all asset prices through the term structure of interest rates. This book will create a better understanding of that monetary policy so both students and professionals can get a solid understanding of this term structure relationship and how it works throughout the financial system. "-- Provided by publisher.
Machine generated contents note: Preface Chapter 1: Introduction What You Will Learn In This Chapter Overview Where We Are Going in This Book Contributions Made By the Financial System Recurring Themes in the Chapters Ahead Resources Chapter 2: Overview of the Financial System What You Will Learn In This Chapter Introduction Features of An Effective Financial System Direct Methods of Finance Indirect Methods of Finance Primary versus Secondary Markets Chapter 3: The Special Role of Commercial Banks What You Will Learn In This Chapter Background Commercial Bank Balance Sheet Payment System and Money Liquidity Provision Dealing with Asymmetric Information Maturity Transformation The Safety Net and Regulatory Policy Chapter 4: The Pricing of Financial Assets What You Will Learn In This Chapter Background Present Value Maturity and Price Sensitivity Holding Periods versus Maturities Return versus Yield Duration Nominal versus Real Yields Appendix A: Variations Of The Valuation Relationship Appendix B:Solutions Using A Financial Calculator Chapter 5: Factors Affecting Yields What You Will Learn In This Chapter Background The Term Structure of Interest Rates Credit Risk Liquidity Taxation Embedded Options Flights to Safety Chapter 6: Principles of Portfolio Selection and Efficient Markets What You Will Learn In This Chapter Overview Uncertainty, Expected Return, and Risk Selecting a Portfolio Efficient Portfolops And Risk-Return Trade-Offs Efficient Markets Hypothesis Chapter 7: The Money Market What You Will Learn In This Chapter Background and Basic Features of the Money Market Pricing Treasury Bills The Role of Commercial Banks in the Money Market Letters of Credit and Bankers Acceptances Monetary Policy Effects on the Money Market Chapter 8: The Bond Market What You Will Learn In This Chapter Background Treasury Notes and Bonds Corporate Bonds Munis Government-Sponsored Enterprises (GSEs) The Impact of Monetary Policy on the Bond Market Chapter 9: Securitization What You Will Learn In This Chapter Background Obstacles to Overcome Beginnings of Securitization-MBS Other Securitized Loans-Consumer ABS ABS Involving Business Credit-CDOs and Structured Securities Securitization and the Integration of Credit Markets Monetary Policy and Securitization Chapter 10: The Mortgage Market What You Will Learn In This Chapter Background Home Mortgages Commercial Mortgages The Mortgage Market and Monetary Policy Chapter 11: The Equity Market What You Will Learn In This Chapter Background Equities as a Source of Corporate Finance Preferred versus Common Shares Primary and Secondary Markets Valuation of Individual Shares Price-earnings Extending These Principles to the Stock Market Monetary Policy and the Stock Market Indexes of Stock Prices Chapter 12: Central Banking and the Federal Reserve What You Will Learn In This Chapter Background Origins of Central Banks Constitutional Foundations The Century And A Quarter Without A Central Bank Creation of the Federal Reserve Early Years of the Federal Reserve Reforms of the 1930s Fed Independence Central Bank Accountability and Transparency Central Bank Responsibilities Monetary Operations Chapter 13: Monetary Policy: The Basics What You Will Learn In This Chapter Background The Operational Counterparts to Maximum Employment and Price Stability Aggregate Demand and Aggregate Supply The Model Addressing Inflation Addressing a Shortfall in Output Okun's Law Chapter 14: Monetary Policy: Challenges Faced by Policymakers What You Will Learn In This Chapter Background Other Forces Affecting Output and Inflation Lags and Other Complications Policy Rules Expectations and Central Bank Credibility Inflation Targeting The Zero-Bound Constraint and the Slow Recovery from the Great Contraction Chapter 15: Financial Crises What You Will Learn In This Chapter Background Classic Banking Panics The Nightmare of the Great Depression The Financial Crisis Common Threads Chapter 16: The Foreign Exchange Market and Exchange Rate Regimes What You Will Learn In This Chapter Background Features of the Market The Relation Between Spot and Forward Exchange Rates Long Run Exchange Rate Relationships The Real Exchange Rate Exchange Rate Determination in the Shorter Run Floating Exchange Rate Regime Fixed Exchange Rate Regime Chapter 17: Depository Institutions What You Will Learn In This Chapter Background Organization of Commercial Banks and Other Depository Institutions Economic Functions of Depository Institutions The Balance Sheet of the Commercial Banking System The Balance Sheet of Savings Institutions The Balance Sheet of Credit Unions Deposit Insurance Regulation and Supervision of Depository Institutions Depository Institutions and Monetary Policy Chapter 18: Mutual Funds What You Will Learn In This Chapter Background History SEC Regulation Role of Mutual Fund Complexes Types of Funds Open-End Funds Exchange-Traded Funds Closed-End Funds Mutual Funds and Monetary Policy Chapter 19: Hedge, Venture Capital, and Private Equity Funds What You Will Learn In This Chapter Background Commonalities In Structure Hedge Funds Venture Capital Funds Private Equity Funds Alternative Investment Funds and Monetary Policy Chapter 20: Large Institutional Investors What You Will Learn In This Chapter Background Pension Funds Life Insurance Companies Property and Casualty Insurance Companies Large Institutional Investors and Monetary Policy About the Author Index .
Includes index.
Keywords: Capital market; Banks and banking; Monetary policy; Finance